Assessment of Liver and Kidney Antioxidant Enzymes and Lipid Profiles of Type-1Diabetic Rats Treated with Selected Medicinal Plants - Ayuba, Victoria; Ansari A. Rizwan; Ezekwe, A.S; Chris, A.W; Ejiofor D.C (International Journal of Natural Sciences: Current and Future Research Trends, 2020)
The aim of this study was to evaluate the activity of the liver and kidney antioxidant enzymes as well as the lipid profile of Type-1 diabetic rats treated with methanol leaf extract of cashew (Anacardium occidentale), pawpaw (Carica papaya) and guava (Psidium guajava). Dry Plant leaves were processed into powder. 500 g of the powdered plant sample resulting from each of the plant materials was macerated to form extract. A total of thirty (30) apparently healthy adult male wistar rats were divided into six (6) groups of five (5) rats per group. Fasted rats were induced with Type-1 diabetes by a single intraperitoneal injection of 60 mg/kg b.w of streptozotocin.Group I: Normal control; Group II: Untreated diabetic rats, Group: III-V Diabetic Rats adminstered with 200 mg/kg b.w of methanol leaf extract of Carica papaya, Psidium guajava, Anacardium occidentale orally respectively Group VI: Diabetic rats administered with standard drug (Glibenclamide) orally. Treatment lasted for 28 days. Rats were sacrificed 24hrs after the last treatment. Blood, liver and kidney were harvested and processed. Induction of diabetes significantly elevated the lipid profile and the activity of both liver and kidney antioxidants enzymes. However, administration of 200 mg/kg bw of methanol leaf extract of C. papaya, P. guavaja and A. occidentale to rats in groups III-V respectively resulted in a reduction that was not significantly (P>0.05) different from the values obtained for group VI treated with the standard drug (Glibenclamide). In conclusion, this research reveals that leaves from the studied plants can be explored to offer a helping hand in the management of diabetes related complications.